Antebrachial microvascular flap for reconstruction of the pelvic limb: case report - Banegas-Ruiz, Rodrigo; Valderrama-Treviño, Alan I.; Rivas-Montero, J. A.; Gómez-Mendoza, F. F.; García-Martínez, E.; Baca Domínguez, C. R.; Campos-Angulo, G.; Alejo-Fuentes, L. F.; García-Valadez, L. R.; Jiménez-Nateras, C. N.; Ramos-Lojero, V. M.; Espejel-Blancas, J. A.; et al. (International Journal of Research in Medical Sciences, 2019)
Complex defects in the soft tissues of the foot and ankle caused by high-energy trauma, infection, cancer or diabetes require rapid and effective treatment which decreases the risk of infection, bone healing time, hospital stay and number total of surgical approaches. Authors report a clinical case of a 23-year-old female patient who suffers high-energy trauma due to a motorcycle accident which causes exposure of the distal third of the tibia, loss of the tibial joint face, and loss of tissue throughout the region of the malleolus medial of the right pelvic extremity. Tissue transfer to the pelvic limb is performed using left contralateral radial antebrachial free flap as donor area. This case report aims to emphasize the key aspects of the high energy trauma approach by using microvascular flaps, as well as the satisfactory evolution of the patient that directly affects the prognosis for life and function.